2011
DOI: 10.1111/j.1365-2583.2011.01068.x
|View full text |Cite
|
Sign up to set email alerts
|

Neuropeptide Y-like signalling and nutritionally mediated gene expression and behaviour in the honey bee

Abstract: Previous research has led to the idea that derived traits can arise through the evolution of novel roles for conserved genes. We explored whether Neuropeptide Y-like signaling, a conserved pathway that regulates food-related behavior, is involved in a derived, nutritionally-related trait, division of labor in worker honey bees. Transcripts encoding two NPY-like peptides were expressed in separate populations of brain neurosecretory cells, consistent with endocrine functions. NPY-related genes were upregulated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
72
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(78 citation statements)
references
References 52 publications
6
72
0
Order By: Relevance
“…Rather, given the ecology of N. vespilloides, it is more likely that increased npf is associated with preparation for another bout of reproduction. In other insects npf is associated with an increased motivation to seek a new reproductive resource or mating opportunities [8,30]. It also acts as a signal to reinitiate full reproductive capabilities [27,28], such as yolking up new eggs, or increased motivation to leave a social group [25,31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rather, given the ecology of N. vespilloides, it is more likely that increased npf is associated with preparation for another bout of reproduction. In other insects npf is associated with an increased motivation to seek a new reproductive resource or mating opportunities [8,30]. It also acts as a signal to reinitiate full reproductive capabilities [27,28], such as yolking up new eggs, or increased motivation to leave a social group [25,31].…”
Section: Discussionmentioning
confidence: 99%
“…Feeding pathways have altered gene expression in parenting insects, fish and mammals [8][9][10]. We characterize the expression of a pathway that heavily influences the motivation to eat, neuropeptide F (neuropeptide Y in vertebrates [11]), during parental care in the subsocial burying beetle Nicrophorus vespilloides, an insect with complex parental care [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Bees at three different stages of maturation -nurses, foragers and pre-nursing bees like those used in the microarray experiment -were removed from the hive and fed either a rich or a poor diet for 4days, after which we measured gene expression in the fat bodies. We included diet-and maturation-regulated genes [based on microarray studies or previous qPCR studies (Ament et al, 2008;Ament et al, 2011) (Kim and Rulifson, 2004) and the short neuropeptide F receptor (snpfR) (Root et al, 2011) -for which we did not have previous evidence of differential expression between nurses and foragers or in response to diet. We confirmed that all 10 genes were differentially expressed between nurses and foragers (Fig.3).…”
Section: Maturational Changes In Fat Body Transcriptomic Responsivenementioning
confidence: 99%
“…qPCR was performed as described previously (Ament et al, 2011). cDNA was synthesized from 200ng total RNA.…”
Section: Quantitative Pcr (Qpcr)mentioning
confidence: 99%
“…, Human recombinant Zinc, Gibco, Grand Island, NY, USA) and control bees received 1 µl of Hepes buffer solution (25 mmol l −1 ) (Ament et al, 2011). Solutions were used immediately after melting and kept in ice during the procedure.…”
Section: Experimental Series and Injectionsmentioning
confidence: 99%